Implementation of Game Models to Improve Coordination of Children Participating in Traditional Sports Extracurricular Activities - Natasya Nurlaila Firdaus; Anggi Setia Lengkana; Tedi Supriyadi (Journal of Physical Education Health and Sport, 2026)
Motor coordination is an essential component of adolescent physical development; however, traditional sports extracurricular programs often employ repetitive and less structured training methods that limit optimal motor skill development. This study aimed to determine the effectiveness of a game-based learning model in improving motor coordination among students participating in traditional sports extracurricular activities. The study used a one-group pretest-posttest design and a quasi-experimental methodology. Purposive sampling was used to choose 30 students between the ages of 15 and 17. Over the course of four weeks, observations, documentation, and motor coordination tests (hand-eye and foot-eye coordination) were used to gather data. Descriptive statistics and the paired sample t-test were used to analyze the data. The mean scores for hand-eye coordination and foot-eye coordination increased from 14,37 to 17,37 and 3,03 to 3,67, respectively, according to the data. The results of the hypothesis test indicate a significance level of 0,000 (p<0,05), which indicates a significant difference between the pre-test and post-test. In addition, the effect size indicates a large category for hand-eye coordination (d=0,88) and a medium category for foot-eye coordination (d=0,72). In conclusion, the game-based learning model can be used as a creative strategy in conventional sports extracurricular programs and is successful in enhancing students' motor coordination.